Hemozoin induces hepatic inflammation in mice and is differentially associated with liver pathology depending on the Plasmodium strain. - Katrien Deroost; Natacha Lays; Thao-Thy Pham; Denisa Baci; Kathleen Van den Eynde; Mina Komuta; Mauro Prato; Tania Roskams; Evelin Schwarzer; Ghislain Opdenakker; Philippe E Van den Steen (PLoS ONE, 2014)
Malaria is a global disease that clinically affects more than two hundred million people annually. Despite the availability of effective antimalarials, mortality rates associated with severe complications are high. Hepatopathy is frequently observed in patients with severe malarial disease and its pathogenesis is poorly understood. Previously, we observed high amounts of hemozoin or malaria pigment in livers from infected mice. In this study, we investigated whether hemozoin is associated with liver injury in different mouse malaria models. C57BL/6J mice infected with the rodent parasites Plasmodium berghei ANKA, P. berghei NK65 or P. chabaudi AS had elevated serum liver enzymes without severe histological changes in the liver, in line with the observations in most patients. Furthermore, liver enzymes were significantly higher in serum of P. chabaudi AS-infected mice compared to mice infected with the P. berghei parasite strains and a strong positive correlation was found between hepatic hemozoin levels, hepatocyte damage and inflammation in the liver with P. chabaudi AS. The observed liver injury was only marginally influenced by the genetic background of the host, since similar serum liver enzyme levels were measured in infected C57BL/6J and BALB/c mice. Intravenous injection of P. falciparum-derived hemozoin in malaria-free C57BL/6J mice induced inflammatory gene transcription in the liver, suggesting that hemozoin may be involved in the pathogenesis of malaria hepatopathy by inducing inflammation.